PERANCANGAN SISTEM INFORMASI INVENTORY MENGGUNAKAN MICROSOFT VISUAL STUDIO 2010 DAN MYSQL DI PT. ABC KOGEN DAIRY - Eric Kurniawan Prayoga; Rina Kurniawati (INFOKOM (Informatika & Komputer), 2021)
Inventory Information system is a system for storing goods to achieve a goal in decision making by receiving input and producing output using a simple transformation. The inventory system usually consists of a system for receiving incoming goods, outgoing goods, and a warehouse or inventory system. Over time, an inventory Information system is needed to manage data precisely and efficiently.Therefore, the author designed an inventory Information system to help the work at PT. ABC Kogen Dairy.The design of this inventory Information system uses the Microsoft Visual Studio 2010 programming language with MySql database.Data collection techniques used are through observation, interviews and literature studies related to the subject matter. The development method used is the Waterfall Model. The goal is to make the inventory system newer, more responsive in managing data and Information in and out of goods, simplifying the performance of users who work, and being able to follow technological developments.